2017
DOI: 10.1002/2016jg003511
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between substrate availability, dissolved CH4, and CH4 emissions in an arctic wetland subject to warming and plant removal

Abstract: The Arctic is warming which may potentially affect substrate availability, organic matter decomposition, plant growth, and plant species composition. This may lead to changes in the exchange of methane (CH4) and carbon dioxide (CO2) between the soil system and the atmosphere. Yet the correlations among substrate availability, CH4 production, and net emissions of CH4 have been scarcely studied in arctic wetlands. Presently, the impact of increasing temperatures on CH4 exchange is uncertain as the two existing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…In turn, such reductions would result in no net shift in NEE if heterotrophic respiration is similarly reduced. In partial support of this, Nielsen et al (2017) found that NEE was unresponsive to shrub removal and its interaction with experimental summer warming in a Greenland fen. Pairing plant removal (Díaz, Symstad, Chapin, Wardle, & Huenneke, 2003) and global change experiments can thus provide important information on how global 4.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In turn, such reductions would result in no net shift in NEE if heterotrophic respiration is similarly reduced. In partial support of this, Nielsen et al (2017) found that NEE was unresponsive to shrub removal and its interaction with experimental summer warming in a Greenland fen. Pairing plant removal (Díaz, Symstad, Chapin, Wardle, & Huenneke, 2003) and global change experiments can thus provide important information on how global 4.…”
Section: Introductionmentioning
confidence: 79%
“…carbon, ecosystem respiration, global warming, gross primary productivity, leaf area index, normalized difference vegetation index, plant-plant interactions change factors may mediate plant-plant interactions to influence high latitude terrestrial ecosystem processes (Aerts, 2010;Nielsen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The water-air partitioning of FA and AA can be estimated from Eq. (3) using measured soil temperature and pH, effective Henry's law constants, and estimated soil formate and acetate concentrations (formate and acetate were chosen as 2 mg L −1 , probably an upper limit for this region; Nielsen et al, 2017;Ström et al, 2012). Further uncertainty is introduced by using literature values for soil formate and acetate concentrations because it requires making the assumption that all the formate and acetate extracted from the soils in those studies resided in the soil pore water, which is unlikely to be the case.…”
Section: Soil Emissionsmentioning
confidence: 99%
“…A very acidic soil would also promote the emission of FA and AA, but the soil samples were taken from three different microenvironments (albeit all within ∼ 5 km of the station), and all samples had near-neutral pH. Additionally, other work examining Arctic soils has generally found near-neutral pH (Brummell et al, 2012;Nielsen et al, 2017). While a combination of lower pH and higher soil reservoirs of formate and acetate could perhaps lead to somewhat larger emissions than those estimated here, we conclude that equilibrium soil-air partitioning is unlikely to account for the high mixing ratios of FA and AA observed in this study.…”
Section: Soil Emissionsmentioning
confidence: 99%
See 1 more Smart Citation